Archive Records Management System (ARMS): Functional Requirement - binti Zulkipli, Fatin Nur; Mat Yatin, Saiful Farik; Hunssai, Nurussobah; bin Mostakim , Muhammad Syawal; binti Tengku Hisham, Tengku Nisa Zahirah (Record and Library Journal, 2021)
Background of the Study: This paper present the functional requirement in Archive Records Management System (ARMS) that provide a comprehensive record keeping management system based on the organization function according to the business activities and process. Purpose: The purpose of this article is to describe the core functional requirement for record keeping system to support users in performing their task that related to electronic record management system. Method: The method used in this article are based on the previous research, guidelines and standards. Findings: Furthermore, this article similarly aim to evaluate and identify the core functional requirement of archive records management system based on the standards use. This article intent to make user aware towards the core functional requirement in managing electronic records system to fulfil the needs and meet based on proper requirements. Subsequently, through completion this article, the research limitation and difficulties in this study is there are too many requirement of electronic record keeping system available that make users are confused to differentiate between requirements. Meanwhile, the user does not know to choose the right requirement that meet organization function and activities. Other than that, it is quite hard to keep core functional requirement sustain in line with the compliance in organization. Conclusion: The originality this article is to provide a clear content and original requirement based on Archive Records Management System implementation for record professional to recognize the high levels of competencies as well as effectiveness reflection in handling Archive Record Management System (ARMS).